Morphometric and egg characteristics of indigenous ducks - P K Vij; M S Tantia; S Pan; R K Vijh (Journal of Livestock Biodiversity, 2025)
Observations were recorded from 89 flocks of indigenous ducks reared by farmers in 13 districts of 4 states viz. Nadia, North 24 Parganas and Hooghly of West Bengal; Puri, Cuttack, Kendrapara and Khurda of Orissa, Alappuzha, Pathanamthitta, Kottayam and Kollam of Kerala; and Krishna and West Godawari of Andhra Pradesh to study management practices, morphological characters, body biometry and egg quality parameters. It was observed that indigenous ducks are reared by local poor people following backyard system. These are maintained in community ponds in West Bengal and Orissa and along with paddy cultivation in an integrated farming system in Kerala and Andhra Pradesh. The local ducks are medium in size and have wide variation in plumage colour, mainly brown mixed with other colours. The ducks of Kerala and Andhra Pradesh are morphologically similar. In Kerala, native ducks are known as Chara and Chemballi on the basis of plumage colour. Head width, bill length, bill width, body girth, wing span and shank length averaged 3.02±0.03, 5.25±0.04, 3.21±0.02, 30.07±0.31, 81.58±0.52 and 5.67±0.05cm respectively. Drakes had significantly higher (p≤ 0.01) body measurements than ducks. Effect of location/state was significant on head width, bill length, bill width, body girth and shank length. Average adult body weight was 1.40±0.02kg and it was significantly affected by sex and location/state. Egg weight averaged 62.75±0.54g. Average values for albumen index, yolk index and haugh units were 0.109±0.002, 0.388±0.004 and 87.422±0.713 respectively